Factors associated with metabolically healthy status in obesity, overweight, and normal weight at baseline of ELSA-Brasil. Issue 27 (July 2016) - Diniz, Maria de Fátima Haueisen Sander; Beleigoli, Alline Maria Rezende; Ribeiro, Antônio Luiz P.; Vidigal, Pedro Guatimosim; Bensenor, Isabela M.; Lotufo, Paulo A.; Duncan, Bruce B.; Schmidt, Maria Inês; Barreto, Sandhi Maria
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The primary aim of this study was to evaluate metabolically healthy status (MHS) among participants in obesity, overweight, and normal weight groups and characteristics associated with this phenotype using baseline data of Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). The secondary aim was to investigate agreement among 4 different MHS criteria. This cross-sectional study included 14, 545 participants aged 35 to 74 years with a small majority (54.1%) being women. Of all participants, 22.7% (n = 3298) were obese, 40.8% (n = 5934) were overweight, and 37.5% (n = 5313) were of normal weight. Socio-demographic, behavioral, and anthropometric factors related to MHS were ascertained. Logistic regression models estimated the odds of associations. We used 4 different criteria separately and in combination to define MHS: the National Health and Nutrition Examination Survey (NHANES), the National Cholesterol Education Program (NCEP-ATPIII), the International Diabetes Federation (IDF) and comorbidities, and the agreement between them were evaluated by Cohen-kappa coefficient. MHS was present among 12.0% (n = 396) of obese, 25.5% (n = 1514) of overweight, and 48.6% (n = 2582) of normal weight participants according to the combination of the 4 criteria. The agreement between all the 4 MHS criteria was strong (kappa 0.73 P  < 0.001). In final logistic models, MHS was associated with lower age, female sex, lower body mass index (BMI), and weight change from age 20 within all BMI categories. This study showed that, despite differences in prevalence among the 4 criteria, MHS was associated with common characteristics at every BMI category.